Using Mothur to Determine Bacterial Community Composition and Structure in 16S Ribosomal RNA Datasets. Issue 1 (20th June 2019) - Chappidi, Sruthi; Villa, Erika C.; Cantarel, Brandi L.
Abstract: The 16S ribosomal RNA (rRNA) gene is one of the scaffolding molecules of the prokaryotic ribosome. Because this gene is slow to evolve and has very well conserved regions, this gene is used to reconstruct phylogenies in prokaryotes. Universal primers can be used to amplify the gene in prokaryotes including bacteria and archaea. To determine the microbial composition in microbial communities using high‐throughput short‐read sequencing techniques, primers are designed to span two or three of the nine variable regions of the gene. Mothur, developed in 2009, is a suite of tools to study the composition and structure of bacterial communities. This package is freely available from the developers (https://www.mothur.org ). This protocol will show how to (1) perform preprocessing of sequences to remove errors, (2) perform operational taxonomic unit (OTU) analysis to determine alpha and beta diversity, and (3) determine the taxonomic profile of OTUs and the environmental sample. © 2019 The Authors.